Faktor Angiogenik Sebagai Biomarker Pada Pathogenesis Preeklamsia - Fitrya Ayu Anggraini (Politeknik Karya Husada, 2022)
Preeclampsia is a disease that occurs in 3% - 7% of pregnant women in the world. Preeclampsia and eclampsia after 20 weeks of gestation, up to 25% of cases development after delivery, most common within the first 4 days but occasionally up to 6 weeks postpartum. Untreated preeclampsia usually gets worse over a variable period of time, then suddenly progresses to eclampsia, which occurs in 1/200 patients with preeclampsia. Untreated eclampsia is leading to severity. Objective: The aim of this study was to determine angiogenic factors as biomarkers in the pathogenesis of preeclampsia. This study was conducted using the scooping review method on studies published in early 2010-2021. The search was carried out using available databases including Scopus, Science Direct, PubMed, Google Scholar. The keywords used included angiogenic factors, pathogenesis and preeclampsia. The results showed that the pathonegenesis of preeclampsia is a decrease in VEGF, PlGF, and an increase in sFlt-1 so that it can be used as an early detector of preeclampsia as well as a biomarker in preeclampsia research.